1989
DOI: 10.1002/pola.1989.080270327
|View full text |Cite
|
Sign up to set email alerts
|

Associative organotin polymers. I. Symmetric trialkyltin fluorides: Synthesis and properties

Abstract: SynopsisFour novel symmetric tri-n-alkyltin fluorides were prepared. In this homologous series, melting point decreases with increase in the carbon chain length while an x-ray diffraction study shows an increase in amorphousness. 'H-NMR spectra in cyclohexane, a nonpolar solvent in which these compounds form long polymeric chain, show a peak broadening effect due to high solution viscosity at very low solute concentration. Contrary to this, the spectra in CDCI,, a polar solvent in which these compounds are mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Furthermore, in the presumed polymeric triorganotin fluorides, R 3 SnF (R ϭ Me, Et, nPr, nBu, nPen, nHex, nOct, nDec), the effect of the lengths of the alkyl chain on the melting point, solubility, and the degree of crystallinity were studied, however, without the support of spectroscopy. [58] Recently, Gillespie et al used results from ab initio calculations to reinterpret the nature of bonds containing fluorine. [59] They concluded that a large majority of elementϪfluorine bonds, including SiϪF bonds, possess substantial ionic character, and molecules such as SiF 4 are therefore more appropriately described using a ligand closepacking model with predominately ionic SiϪF bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the presumed polymeric triorganotin fluorides, R 3 SnF (R ϭ Me, Et, nPr, nBu, nPen, nHex, nOct, nDec), the effect of the lengths of the alkyl chain on the melting point, solubility, and the degree of crystallinity were studied, however, without the support of spectroscopy. [58] Recently, Gillespie et al used results from ab initio calculations to reinterpret the nature of bonds containing fluorine. [59] They concluded that a large majority of elementϪfluorine bonds, including SiϪF bonds, possess substantial ionic character, and molecules such as SiF 4 are therefore more appropriately described using a ligand closepacking model with predominately ionic SiϪF bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Perfect regioselectivity was observed with arylacetylenes ( 1e – g ) (entries 6–8), and functionalized aliphatic alkynes ( 1h , i ) were efficiently converted to the products ( 4ha , ia ) (entries 9 and 10). Furthermore, trioctyltin fluoride ( 3b ) , could participate in the reaction, where 1d , e were transformed with efficacy similar to that with 3a (entries 11 and 12). In addition to 1h , i , aliphatic terminal alkynes having a C–Cl bond ( 1j ) or silyl ether ( 1k ) also afforded the borylstannylation products ( 4hb – kb ) with these functional groups intact, although the regioselectivities dropped to some extent in comparison to that with 1d (entries 13–16) .…”
Section: Resultsmentioning
confidence: 99%
“…13 C NMR (CDCl3) δ 11.83 (JC-Sn = 328.3 Hz), 14. 12,22.65,22.71,24.75,26.99,27.08,27.17,28.88,29.07,29.31,29.37,29.45,29.78,31.86,31.98,34.53,40.50,45.44,82.99 (major), 83.25 (minor), 149.73, 177.79. 119 Sn NMR (CDCl3) δ -56.12 (major), -68.57 (minor).…”
Section: Methodsmentioning
confidence: 99%
“…x ‫ס‬ mole fraction styrene in copolymer y ‫ס‬ mole fraction fluoracrylate in copolymer z ‫ס‬ z coordinate, L, m ‫ס‬ non-Newtonian fluid viscosity, m/Lt, Pa-sec ‫ס‬ Newtonian fluid viscosity, m/Lt, Pa-sec c ‫ס‬ cylinder density, m/L 3 , g/cm 3 f ‫ס‬ fluid density, m/L 3 , g/cm 3 ‫ס‬ shear stress, m/Lt 2 , N/m 2…”
Section: Nomenclaturementioning
confidence: 99%
“…The primary obstacle that has hindered the efforts of numerous investigators has been the extremely low CO 2 -solubility of candidate thickeners. 1 Most of the pioneering efforts in this area were conducted by Heller and coworkers [1][2][3][4][5][6] in their evaluation of tri-alkyl tin fluorides, polymers, telechelic ionomers, and 12-hydroxystearic acid. Significant contributions were also made by Irani and coworkers, who successfully thickened CO 2 using silicone-based polymers that required the addition of an organic solvent.…”
Section: Introductionmentioning
confidence: 99%